2004
DOI: 10.1348/0261510041552756
|View full text |Cite
|
Sign up to set email alerts
|

Lonely in the crowd: Recollections of bullying

Abstract: This study examined the long-term correlates of victimization in school with aspects of functioning in adult life, using a specially designed Retrospective Bullying Questionnaire, which also included questions about short-term effects (e.g. suicidal ideation and intrusive memories) and victimization experiences in adulthood. Current relationship quality was assessed in terms of self-perception, attachment style and friendship quality. In total, 884 adults (35% male) from two occupations (teacher, student) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
161
3
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(201 citation statements)
references
References 29 publications
11
161
3
12
Order By: Relevance
“…Previous studies have reported that victims are likely to have fewer friends outside of school than non-involved adolescents or have more difficulties in maintaining friendships (Schäfer et al 2004). Our study may add to that information as it shows that it is probably true for victims but not for bully-victims.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that victims are likely to have fewer friends outside of school than non-involved adolescents or have more difficulties in maintaining friendships (Schäfer et al 2004). Our study may add to that information as it shows that it is probably true for victims but not for bully-victims.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire contains several sections with a total of 44 items (Schafer et al, 2004). Participants are asked to answer questions about their experiences during primary school and secondary school/college.…”
Section: Retrospective Bullying Questionnaire (Rbq)mentioning
confidence: 99%
“…Students who reported that they were exposed to bullying through the period of both the lower and upper grades of primary school were more likely to develop psychological problems compared to those who were exposed to bullying in one of these two periods (during the lower grades of elementary school or only in the higher grade) (54).…”
Section: Introductionmentioning
confidence: 90%
“…The duration of exposure to violent behavior is another significant factor in the development of long-term psychological consequences in individuals exposed to violent behavior (54). Students who reported that they were exposed to bullying through the period of both the lower and upper grades of primary school were more likely to develop psychological problems compared to those who were exposed to bullying in one of these two periods (during the lower grades of elementary school or only in the higher grade) (54).…”
Section: Introductionmentioning
confidence: 99%